A Hybrid K-Means and Agglomerative Hierarchical Clustering Method for Zakat Mal Recipient Classification - Hafidh Asyi; Mulyadi; Hendrawaty (PT. Literasi Teknologi Informatika, 2026)
Grouping and determining zakat mal recipients is an important stage in the accurate and precise distribution of zakat mal. The process of determining zakat mal recipients needs to be taken into account considering that the number of zakat mal recipients in Aceh Besar exceeds the available quota in each zakat mal distribution period in 2022. This research aims to using KnA method in the process of determining zakat mal recipients. This research uses criteria data that has been determined by Baitul Mal Aceh Besar for 17 groups of zakat mal recipients. The KnA method is used to rank zakat recipients mal in the process of determining zakat mal recipients based on criteria for each group. Testing the results of the KnA method was carried out by assessing using original data on five zakat mal recipients for each group. The results of this research show that there are five groups with five zakat mal recipients in the same order with a percentage of 29%, three groups with three zakat mal recipients in the same order with a percentage of 17%, four groups with two zakat mal recipients in the same order with a percentage of 23%, four groups with one zakat mal recipient in the appropriate order with a percentage of 23%, and two groups with zero zakat mal recipients in the appropriate order with a percentage of 11%. Based on the research results, it can be concluded that the use of the KnA method in determining zakat mal recipients has a relatively low level of accuracy with only five of the seventeen groups in the appropriate order for five sample data with an accuracy percentage of 29%.